Exkludering som fält — inkludering som uppdrag: Om uppdragsetnologen som reflexiv pedagog - Pripp, Oscar (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2007)
Ethnological methods are well suited for exploring and explaining structural discrimination within different kinds of social institutions. The ethnologist has various opportunities to study the mechanisms of exclusion that are difficult to identify on an everyday micro level, and link this empirical level to structures on a macro level. In this article I discuss four different mechanisms of exclusion within the state-financed public culture sector: insufficient knowledge concerning diversity management, recruitment by networks and strong ties, ambiguity and ambivalence. I also discuss in what manner the results of this research can be used to affect the policies of authorities and institutions/departments. Ethnology and aesthetic culture share common ground in hermeneutic, and the article points out the ethnologist as an actor of change and a reflexive pedagogue. This is illustrated by examples of how you can get the principals to set about the results and put them in action.